“Right on all Occasions?” – On the Feasibility of Laterality Research Using a Smartphone Dichotic Listening Application - Bless, Josef J.; Westerhausen, René; Arciuli, Joanne; Kompus, Kristiina; Gudmundsen, Magne; Hugdahl, Kenneth (Frontiers in Psychology, 2013)
Most psychological experimentation takes place in laboratories aiming to maximize experimental control; however, this creates artificial environments that are not representative of real-life situations. Since cognitive processes usually take place in noisy environments, they should also be tested in these contexts. The recent advent of smartphone technology provides an ideal medium for such testing. In order to examine the feasibility of mobile devices in psychological research in general, and laterality research in particular, we developed a mobile device (MD) version of the widely used speech laterality test, the consonant-vowel dichotic listening (DL) paradigm, for use with iPhones/iPods. First, we evaluated the retest reliability and concurrent validity of the DL paradigm in its MD version in two samples tested in controlled, laboratory settings (Experiment 1). Second, we explored its ecological validity by collecting data from the general population by means of a free release of the MD version (iDichotic) to the App Store (Experiment 2). The results of Experiment 1, indicated high reliability (rICC=0.78) and validity (rICC=0.76 to 0.82) of the MD version which consistently showed the expected right-ear advantage (REA). When tested in real-life settings (Experiment 2), participants (N=167) also showed a significant REA. Importantly, the size of the REA was not dependent on whether the participants chose to listen to the syllables in their native language or not. Together, these results establish the current MD version as a valid and reliable method for administering the DL paradigm both in experimentally controlled as well as uncontrolled settings. Furthermore, the present findings support the feasibility of using smartphones in conducting large-scale field experiments.